Psikologi Humanistik Abraham Maslow pada Tokoh Utama dalam Kisah Nabi Ibrahim a.s. / Abraham Maslow's Humanistic Psychology in the Main Character of Prophet Ibrahim's Story - Ahmad Zainal Mustofa; Nurus Syarifah (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
يصف هذا المقال دراسة الشخصية الرئيسية في قصة النبي إبراهيم عليه السلام التي تم استكشافها من خلال النظرية النفسية الإنسانية لأبراهام ماسلو. قصة النبي ابراهيم عليه السلام هو شكل من أشكال العمل الأدبي الذي يقوم على القرآن. النبي ابراهيم عليه السلام باعتباره كالشخصية الرئيسية في القصة لديها شخصية قوية وعظيمة وشجاعة وليس من السهل أن تشكو، وهذا هو المفتاح الرئيسي لتحقيق ذاته وللوصول إلى ذروة الحاجات. شخصيته مثيرة للاهتمام للدراسة مع النظرية النفسية الإنسانية لأبراهام ماسلو. هذه النظرية هي إحدى النظريات النفسية للشخصية التي تقترح خمسة مستويات من الاحتياجات البشرية، من الاحتياجات الأساسية إلى ذروة الاحتياجات. هذا البحث هو البحث المكتبي  (library research) باستخدام المنهج الوصفي التحليلي. تشير نتائج هذه الدراسة إلى أن التسلسلات الهرمية الخمسة للاحتياجات الواردة في النظرية النفسية الإنسانية لأبراهام ماسلو قد تم تحقيقها في شخصية النبي إبراهيم عليه السلام، والتي انعكست في السفر والتفاعلات الاجتماعية التي حدثت خلال حياته. الاحتياجات الخمسة هي الحاجة الفسيولوجية، والحاجة إلى الأمن، والحاجة إلى الحب والانتماء، والحاجة إلى الاحترام والحاجة إلى تحقيق الذات.الكلمات المفتاحية:  قصة النبي إبراهيم عليه السلام، والنظرية النفسية الإنسانية لأبراهام ماسلو، والتسلسل الهرمي للاحتياجات الخمسةAbstractThis article describes the study of the main character in the story of Prophet Ibrahim a.s. which explored through Abraham Maslow's theory of humanistic psychology. The story of Prophet Ibrahim a.s. is a form of literary work that is based on the Al-Qur'an. Prophet Ibrahim a.s. as the main character in the story has a strong and not easy to complain personality, which is the key to achieving self-actualization. His personality is interesting to study with Abraham Maslow's theory of humanistic psychology. This theory is one of the psychological theories of personality which proposes five levels of human needs, from basic needs to peak needs. This research is a library research using descriptive analytical method. The results of this study indicate that the five hierarchies of needs contained in Abraham Maslow's theory of humanistic psychology are fulfilled in the personality of Prophet Ibrahim a.s, both reflected in the travel and social interactions that occurred during his lifetime. The five needs are physiological needs, security needs, compassion needs, appreciation needs and self-actualization needs.